2015
DOI: 10.1039/c4ra14802a
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Ag2O nanoparticle incorporated mesoporous silica with large bottle-neck like mesopores for the aerobic oxidative synthesis of disulfide

Abstract: Ag2O nanoparticle supported on silica with large bottle-neck like mesopores for the aerobic oxidative synthesis of disulphides in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 72 publications
0
12
0
1
Order By: Relevance
“…Figure 5b shows that exposure of the thiol solution to ambient air for 24 hours leads to the near-complete conversion of 3 to its disulfide, as evidenced by the appearance of a S−S signal between 480-550 cm −1 and the disappearance of the S−H signal at 2570 cm −1 . 79 Further bubbling of O2 for 1 hour led to the loss of the disulfide signal and the appearance of absorption at 1070 cm −1 characteristic of =S=O species (Figure 5b). The sharp peak in the FTIR spectrum of 2 is assigned to the C=O stretching present in this ester molecule, consistent with that observed in Nikolić et al 80 The region between 700 and Consistent with FTIR measurements, exposing a thiol solution of 3 to air for 24 hours showed high coverages of ferrocene molecules in cyclic voltammetry, indicating a high density monolayer (Figure 5c).…”
Section: Conversion Of Thiols To Disulfidesmentioning
confidence: 99%
“…Figure 5b shows that exposure of the thiol solution to ambient air for 24 hours leads to the near-complete conversion of 3 to its disulfide, as evidenced by the appearance of a S−S signal between 480-550 cm −1 and the disappearance of the S−H signal at 2570 cm −1 . 79 Further bubbling of O2 for 1 hour led to the loss of the disulfide signal and the appearance of absorption at 1070 cm −1 characteristic of =S=O species (Figure 5b). The sharp peak in the FTIR spectrum of 2 is assigned to the C=O stretching present in this ester molecule, consistent with that observed in Nikolić et al 80 The region between 700 and Consistent with FTIR measurements, exposing a thiol solution of 3 to air for 24 hours showed high coverages of ferrocene molecules in cyclic voltammetry, indicating a high density monolayer (Figure 5c).…”
Section: Conversion Of Thiols To Disulfidesmentioning
confidence: 99%
“…The S-H bond stretch, ν(SH), is typically present in the 2500-2600 cm -1 range as shown in the IR spectrum in Figure 2a. 28 This is evident in the spectrum of PhSH whereas this peak is absent in the spectra of PTS, PPS, and PHS marking the conversion of the thiol into corresponding polysulfides. Characteristic peaks of the phenyl polysulfide bonds are visible in the 400-550 cm -1 region (supporting Figure S2).…”
Section: Resultsmentioning
confidence: 97%
“…[6] However, the disulfides are stable and noncorrosive and catalyst non-poisonous. [7] Therefore, to utilize the reaction of disulfide and aldehyde through the cleavage of the SÀ S bond via reductive or oxidative strategy have been reported extensively in recent years (Scheme 1). For example, in 2015, Mukhopadhyay et al reported an O 2 oxidizing method to synthesize benzothiazoles by the SÀ S bond cleavage of 2,2'disulfanediyldianilines using a silica-supported heterogeneous catalyst (MCM-PP) in water.…”
Section: Introductionmentioning
confidence: 99%